ChemInform Abstract: Protecting Group Directed Cyclization: Asymmetric Synthesis of Both cis‐ and trans‐Dihydrexidine from a Common Precursor. Issue 9 (4th March 2014) - Malhotra, Rajesh; Chakrabarti, Sagar; Dey, Tushar K.; Dutta, Swarup; Alapati, Krishna Babu; Dutta, Shantanu; Roy, Subho; Basu, Sourav; Hajra, Saumen
Abstract For the first time a divergent and scalable synthesis of the dimethyl ethers (II) and (VI) of the title compounds is described starting from L‐serine derived materials.